2022
DOI: 10.1039/d2nr01890j
|View full text |Cite
|
Sign up to set email alerts
|

Highly stable, stretchable, and versatile electrodes by coupling of NiCoS nanosheets with metallic networks for flexible electronics

Abstract: The rapid development of portable electronics has contributed to an urgent demand for versatile and flexible electrodes of wearable energy storage devices and pressure sensors. We fabricate a stretchable electrode...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…The initial capacitance values ( C 0 ) of the TPU fiber-based sensor, the TPU@IL 1.7 ionogel fiber-based sensor, and the TPU@IL 2.6 ionogel fiber-based sensor are 0.5 pF, 6 pF, and 12 pF, respectively. The UAC values of these sensors are 464, 456,000, and 656,000 nF·cm –2 , respectively (Figure S4), which are obtained based on galvanostatic charge/discharge curves according to the literature. Clearly, compared with the TPU fiber-based sensor without IL, TPU@IL ionogel fiber-based sensors show significantly improved C 0 and UAC, which helps increase the noise immunity, detection resolution, and device sensitivity. From Figure a, it is found that the TPU fiber-based sensor exhibits a low noise immunity and poor cyclic stability due to the relatively low C 0 and UAC.…”
Section: Resultsmentioning
confidence: 84%
“…The initial capacitance values ( C 0 ) of the TPU fiber-based sensor, the TPU@IL 1.7 ionogel fiber-based sensor, and the TPU@IL 2.6 ionogel fiber-based sensor are 0.5 pF, 6 pF, and 12 pF, respectively. The UAC values of these sensors are 464, 456,000, and 656,000 nF·cm –2 , respectively (Figure S4), which are obtained based on galvanostatic charge/discharge curves according to the literature. Clearly, compared with the TPU fiber-based sensor without IL, TPU@IL ionogel fiber-based sensors show significantly improved C 0 and UAC, which helps increase the noise immunity, detection resolution, and device sensitivity. From Figure a, it is found that the TPU fiber-based sensor exhibits a low noise immunity and poor cyclic stability due to the relatively low C 0 and UAC.…”
Section: Resultsmentioning
confidence: 84%
“…3b). 44,45 In the core-level spectrum of Ni 2p, the peaks located at 855.0 eV and 872.5 eV correspond to Ni 2+ and the peaks positioned at 856.4 eV and 874.1 eV can be assigned to Ni 3+ . Besides, Ni 2p exhibits two shakeup satellite peaks at 861.2 eV and 879.1 eV.…”
Section: Resultsmentioning
confidence: 99%